INTEGRATING FUN AND LEARNIG: THE SUCCESS OF ENGLISH CAMP IN BOOSTING STUDENTS' LANGUAGE CONFIDENCE - Andi Asrifan; Dewi Furwana; Andi Bangsawan; Fadhliyah Rahmah Muin (IAIN Syekh Nurjati Cirebon, 2025)
Proficient English communication is a crucial competency in today's worldwide environment, especially for students seeking to achieve academic and professional success. Traditional English language training techniques in Indonesia frequently prioritize grammar and rote memorization, resulting in insufficient opportunities for authentic language practice and thus diminishing students' confidence and practical application. Immersive programs such as English Camps provide a novel approach, combining organized education with engaging activities. Nonetheless, empirical evidence about their efficacy, especially in resource-constrained environments such as Palopo, is sparse. The English Camp program at SMPIT Insan Madani Palopo markedly enhanced students' confidence in utilizing English via dynamic and engaging activities. Utilizing qualitative data from 150 participants, comprising interviews with students, educators, and tutors, we examined how the integration of enjoyment and learning cultivated a supportive, low-anxiety atmosphere. Significant findings demonstrate an observable rise in students' readiness to engage in communication, less language anxiety, and improved motivation. Logistical constraints and differing competency levels were mitigated by adaptive tactics, including outdoor learning and individualized training. These data highlight the efficacy of English Camps as valuable adjuncts in English language teaching. Such programs can improve both linguistic and psychological outcomes by fostering an immersive, student-centered atmosphere. This study offers significant insights for educators and policymakers, presenting a reproducible approach for enhancing linguistic confidence. Future research ought to investigate the scalability and sustainability of analogous projects to guarantee wider implementation and enduring effects on English language acquisition.